PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN ELEKTRONIK BERBASIS EDMODO TERHADAP HASIL BELAJAR SISWA PADA MATA DIKLAT MELAKUKAN INSTALASI SOUND SYSTEM KELAS XI TEKNIK AUDIO VIDEO DI SMK N 1 KINALI - Wirda Wirda; Almasri Almasri; Sukaya Sukaya (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2014)
The problem in this study is the fact that the field is found in SMK Negeri 1 Kinali, there are many students who obtain a grade XTAV learning outcomes below the minimum standard criteria in subjects perform a Sound System Installation to set the school 73. That is 65.57% of students who under KKM and 34.42% of students who are above KKM. This study uses experimental approach, this study population is a class XI student of SMK Negeri 1 Kinali TAV Academic Year 2014/2015. Experimental class is a class that is treated by using electronic-based instructional media Edmodo and the control class is a class that direct instructional model. Data were analyzed manually to test for normality, homogeneity testing, and hypothesis testing. Test results of research obtained an average value of students who use electronic media-based learning Edmodo is 76.16 while students who use direct instructional model lower 71.20. There is the influence of the use of electronic-based instructional media Edmodo for 6.97% of the student learning outcomes. The results of the hypothesis by using the formula manually in tcount found that 1,886 > 1,677 ttable, so the alternative hypothesis (Ha) is accepted or rejected the nihil hypothesis (Ho). Kata kunci: Media Pembelajaran, Media pembelajaran elektronik berbasis edmodo, Pembelajaran Langsung, Kontrol dan Eksperimen